Supplementing Broiler Quail Diets with Dried Egg Yolk under Heat Stress Conditions - IRMAK, Mehmet; DENLİ, Muzaffer and KAYRİ, Veysi and İPÇAK, Hasan Hüseyin and ODUNCU, Ferhat Mazlum and ALDEMİR, Ezgi (ISPEC Tarım Bilimleri Dergisi, 2024)
This study was conducted to investigate the impact of incorporating dried egg yolk into the diet on the growth performance, carcass quality characteristics, and thigh-breast malondialdehyde value of quails (Coturnix coturnix japonica) subjected to heat stress. A total of 160 quails, 10 days old, were divided into four groups, each comprising 10 replicates with four chicks in each group. Throughout the experiment, the quails were provided with isonitrogenic and isocaloric feeds. The experimental groups were as follows: 1) Basic ration without temperature application (Control); 2) Basic ration with 1% added egg yolk, without temperature application; 3) Basic ration with temperature treatment (30 °C for 8 hours per day); and 4) Basic ration with 1% added egg yolk, along with temperature treatment (30 °C for 8 hours per day). At the end of the experiment, the highest body weight gain occurred in male and female quails which fed the diets incorporated with dried egg yolk and not exposed to heat (P<0.05). The males and females that were exposed to heat and fed with the basic ration showed the lowest feed intake, and this difference was statistically significant (P<0.05). There was no significant difference observed in the malondialdehyde (MDA) values of thigh meat on days 3 and 9, as well as in breast meat on days 3, 6, and 9 (P>0.05). However, a significant change in thigh malondialdehyde value was detected on day 6 (P<0.05). In conclusion, the addition of dried egg yolk to the diets of quails exposed to heat stress diminished the negative effects of heat stress on growth performance.